Applying universal design principles to improve the websites of a selected university - Kamiński, Tomasz; Kapica, Paweł; Dzieńkowski, Mariusz (Journal of Computer Sciences Institute, 2022)
The purpose of the study was to analyze the website of a selected university in terms of usability and accessibility of user interfaces with particular attention to the guidelines of the Web Content Accessibility Guidelines (WCAG) standard. After taking into account all the guidelines, an improved version of the site was created that was free of the diagnosed errors and incompatibilities. Both sites were surveyed using the questionnaire method with the LUT checklist. A survey was also conducted using an eyetracker. Twenty participants took part in this study. The third method of evaluation was to analyze the sites using an automated tool - the WAVE plugin attached to a web browser. The data obtained from the research experiment were analyzed qualitatively and quantitatively. In case of the survey and the WAVE tool, only quantitative analysis was carried out. The results of the analyses carried out using the three methods show unequivocally that the author's website prepared by the authors is clearly better in terms of usability and accessibility than the website of the selected university.